2022
DOI: 10.1021/acsnano.2c01177
|View full text |Cite
|
Sign up to set email alerts
|

Oxide-Derived Core–Shell Cu@Zn Nanowires for Urea Electrosynthesis from Carbon Dioxide and Nitrate in Water

Abstract: Urea electrosynthesis provides an intriguing strategy to improve upon the conventional urea manufacturing technique, which is associated with high energy requirements and environmental pollution. However, the electrochemical coupling of NO 3 − and CO 2 in H 2 O to prepare urea under ambient conditions is still a major challenge. Herein, self-supported core−shell Cu@Zn nanowires are constructed through an electroreduction method and exhibit superior performance toward urea electrosynthesis via CO 2 and NO 3 − c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
94
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(108 citation statements)
references
References 45 publications
(77 reference statements)
0
94
0
Order By: Relevance
“…[16][17][18][19][20][21][22][23][24][25][26][27][28] In comparion with N2 reactant, the superiorities of NO3 − and NO2 − as the reactants are high solubility in aqueous solution, lower dissociation energy of N=O bond (204 KJ mol −1 ), which enable more efficient C−N coupling reaction for urea production. [16][17][18][19][20][21][22][23][24][25][26][27][28] Besides of this, development of high-efficiency electrocatalysts is also critically important for urea synthesis. To date, precious and non-precious metals based electrocatalysts have been fabricated and investigated for electrocatalytic coupling of NO3 − and NO2 − (or NO) and CO2 to efficiently synthesize urea at ambient conditions, exhibiting high electrocatalytic activities.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[16][17][18][19][20][21][22][23][24][25][26][27][28] In comparion with N2 reactant, the superiorities of NO3 − and NO2 − as the reactants are high solubility in aqueous solution, lower dissociation energy of N=O bond (204 KJ mol −1 ), which enable more efficient C−N coupling reaction for urea production. [16][17][18][19][20][21][22][23][24][25][26][27][28] Besides of this, development of high-efficiency electrocatalysts is also critically important for urea synthesis. To date, precious and non-precious metals based electrocatalysts have been fabricated and investigated for electrocatalytic coupling of NO3 − and NO2 − (or NO) and CO2 to efficiently synthesize urea at ambient conditions, exhibiting high electrocatalytic activities.…”
Section: Introductionmentioning
confidence: 99%
“…To date, precious and non-precious metals based electrocatalysts have been fabricated and investigated for electrocatalytic coupling of NO3 − and NO2 − (or NO) and CO2 to efficiently synthesize urea at ambient conditions, exhibiting high electrocatalytic activities. [16][17][18][19][20][21][22][23][24][25][26][27][28][29] In terms to catalytic mechanism research, Zhang et al reported that the formation of *CO and *NH2 intermediates through the adsorption and activation of CO2 and NO on Zn nanobelts catalyst is critically important for subsequent C−N coupling synthesis of urea with a yield rate of 15.13 mmol h −1 g −1 and a faradaic efficiency of 11.26% at ~40 mA cm −2 . 29 Meanwhile, Zhang et al synthesized urea by coupling CO2 with NO2 − on oxygen vacancy-rich ZnO porous nanosheets with a yield rate of 16.56 μmol h −1 and a faradaic efficiency of 23.26% at −0.79 V (vs. RHE).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Up to now, transition metal (TM)-based materials have represented the state-of-the-art electrocatalysts toward the abovementioned nitrogen conversion reactions. Despite the promising catalytic activities displayed by the TM-based materials, a limitation exists in the competition with the hydrogen evolution reaction (HER) because the d electrons prefer to participate in the formation of metal–H bonds . Recent advances demonstrate that p-block-element-based electrocatalysts provide an intriguing picture for nitrogen conversion reactions.…”
Section: Introductionmentioning
confidence: 99%